Robust Impedance Emulation for Transmission Line Interface in Power-Hardware-in-the-Loop Applications: Optimal Filter Approach - Dmitry Rimorov; James Richard Forbes; Olivier Tremblay; Richard Gagnon (IEEE Open Journal of the Industrial Electronics Society)
Power-hardware-in-the-loop (PHIL) simulation infrastructure is an invaluable tool for testing and validating emerging technologies expected to be connected to power grids. As such, PHIL closed-loop stability is a crucial factor to consider when designing its numerical interface. Recent work has shown that the transmission line method provides a robust solution to the PHIL interface stability problem while achieving a high level of PHIL closed-loop performance. However, to fully utilize its advantages, it requires a fast impedance emulation control loop. To solve this problem, this article proposes an $\mathcal {H}_{∞ }$ optimal filter approach for characteristic impedance emulation, which allows a systematic and tractable design procedure and produces a robust controller. Robust stability and performance are assessed through the positive realness check and by virtue of the structured singular value. The proposed method and the resulting controller are compared to an existing approach and validated on a 3-kVA, 208-V PHIL experimental testbed with different types of the device under test, including a residential solar inverter. The results demonstrate significant performance improvements that are crucial for the future megawatt-scale PHIL infrastructure.